2021
DOI: 10.1097/j.pbj.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

Seminal and testicular microbiome and male fertility

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In recent years, 16S rRNA gene sequencing studies using next-generation sequencing techniques (NGS) have shown that human seminal microbiota is mainly composed of four bacterial phyla: Firmicutes, Bacteroidetes, Proteobacteria and Actinobacteria. Although different authors have observed different relative abundances of these phyla, they agree that the most abundant group is Firmicutes [1,2]. The microbial composition at the genus level shows high interindividual variability, with different relative abundances for each taxon; however, the most observed taxa coincide in most cases [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In recent years, 16S rRNA gene sequencing studies using next-generation sequencing techniques (NGS) have shown that human seminal microbiota is mainly composed of four bacterial phyla: Firmicutes, Bacteroidetes, Proteobacteria and Actinobacteria. Although different authors have observed different relative abundances of these phyla, they agree that the most abundant group is Firmicutes [1,2]. The microbial composition at the genus level shows high interindividual variability, with different relative abundances for each taxon; however, the most observed taxa coincide in most cases [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 91%
“…Although different authors have observed different relative abundances of these phyla, they agree that the most abundant group is Firmicutes [1,2]. The microbial composition at the genus level shows high interindividual variability, with different relative abundances for each taxon; however, the most observed taxa coincide in most cases [1][2][3][4][5][6]. Among the most frequently observed genera are Lactobacillus, Corynebacterium, Acinetobacter, Prevotella, Enterococcus, Veillonella, Streptococcus, Porphyromonas, Staphylococcus, Finegoldia, Ralstonia and Pseudomonas.…”
Section: Introductionmentioning
confidence: 94%
“…However, this ideology has recently been challenged by the identification of the presence of a commensal microbial community in the semen of healthy individuals via culture-independent, high-throughput sequencing ( Weng et al, 2014 ; Tomaiuolo et al, 2020 ). According to a comprehensive review, human semen harbors a relatively rich and complex microbial community, and is dominated by bacterial phyla including Actinobacteria, Bacteroides, Firmicutes, and Proteobacteria ( Hou et al, 2013 ; Chen et al, 2018 ; Brandão et al, 2021 ). In addition to the high-throughput sequencing, the Gram staining of human semen samples revealed that there was a greater number of bacterial cells than the total number of sperm cells present in the semen, and these bacterial cells exhibited diverse cell morphologies, supporting the sequencing results and indicating the high microbial community diversity in the semen ( Hou et al, 2013 ).…”
Section: Male Reproductive Tract Microbiomementioning
confidence: 99%
“… Farahani et al (2021) also found a higher prevalence of Ureaplasma urealyticum in infertile men along with a negative association with sperm morphology and concentration ( Farahani et al, 2021 ). However, Lactobacillus has been reported to be associated with improved semen quality ( Farahani et al, 2021 ) and male fertility ( Brandão et al, 2021 ), suggesting that Lactobacillus spp. may be important in sperm development and (or) male fertility.…”
Section: Male Reproductive Tract Microbiomementioning
confidence: 99%
“…A few studies have used sequencing methods to describe the microbiota of the ejaculate, and it is clear that the human ejaculate has a distinctive microbiome 3 . The most common bacteria species found in, the ejaculate belong to Actinobacteria, Bacteroidetes, Firmicutes and Proteobacteria phyla, 3 and most studies have focused on the possible association with male infertility but with conflicting results 2,3 . Further studies on the microbiome of the testis and the ejaculate have been done by culture or PCR methods, 2,13 but the difference in methodologies makes it difficult to directly compare studies.…”
Section: Introductionmentioning
confidence: 99%